Antibiotic Resistance Pattern in Culture Positive Cases of Enteric Fever at Combined Military Hospital Gujranwala - Tanveer, Muhammad; Mehmood, Arshad; Nauman Akbar; Imtiaz Ali (Pakistan Armed Forces Medical Journal, 2026)
Objective: To determine the antibiotic resistance in Blood culture positive cases of enteric fever. Study Design: Cross sectional study Place and Duration of the Study: Combined Military Hospital Gujranwala, Pakistan from Apr 2023 to Mar 2024. Methodology: The study enrolled 290 consecutive patients who were clinically suspected of enteric fever as per inclusion criteria. Blood cultures collected before administration of antibiotics. After identification of salmonella colonies, sensitivity tests for seven antimicrobial agents applied including Ampicillin, Azithromycin, Ceftriaxone, Ciprofloxacin, Cotrimoxazole, Chloramphenicol and Meropenem. Data gathered and analysed for specific resistance along with Multi Drug Resistance (MDR), extended drug resistance (XDR) cases. Results: The study revealed 134(46%) patients as culture positive enteric fever with mean age 25.00 (IQR:13.00) years and 101(75.4%) males, 33(24.6%) females. Resistance pattern identified as Ampicillin in 115(85.8%) cases, Azithromycin in 53(39.6%), Ceftriaxone in 42(31.3%) cases, Ciprofloxacin in 64(47.8%) cases, Chloramphenicol in 61(45.5%), Cotrimoxazole in 61(45.5%) cases. Meropenem showed 100 percent sensitivity and no resistance. the data proved 16.4 % cases as MDR typhoid and 31.34% as XDR cases. Conclusion: Rising incidence of MDR and XDR enteric fever are a major concern. Resistance to Azithromycin and Ceftriaxone is emerging significantly, meropenem should be used cautiously to avoid resistance against it.